The Analysis of Fundamental Variables and Macro Economic Variables in Predicting Financial Distress - Kholisoh, Siti Nur; Dwiarti, Rina (Management Analysis Journal, 2020)
Financial distress is a condition where the company is experiencing financial difficulties prior to bankruptcy. This study aims to identify and explain the influence of the fundamental variables and macroeconomic variables in predicting the probability of financial distress. Based on the eight variables used, current ratio, debt to assets ratio, return on equity and total asset turnover ratio is a fundamental variable. While the sensitivity of inflation, exchange rate sensitivity and interest rate sensitivity included in macroeconomic variables. The population in this study are all porperti and real estate company listed on the Stock Exchange in 2014-2018. The sample selection using purposive sampling technique, acquired 23 companies in the sample with the five companies in the category of financial distress and 18 companies in the category of non financial distress. The analytical method used is logistic regression and sensitivity analysis. The results showed that the variable current ratio, debt to assets ratio, total asset turnover ratio, inflation sesnitivity, exchange rate sensitivity and interest rate sensitivity did not significantly affect the probability of financial distress. While return on equity significantly negative influence on the company’s financial distress.